THE RELATIONS BETWEEN SCIENCE, TECHNOLOGY AND SOCIETY AND CHEMISTRY TEACHING: A LITERARY REVIEW (Interdisciplinary Studies Journal, 2025)
The present work proposed to carry out a literary analysis through scientific productions, in the perspective of knowing what is being developed about STS relations and the teaching of Chemistry. This analysis was made in a temporal cut of the last 5 years, in which it was possible to obtain a number of 12 scientific articles that contemplated the research proposal. After categorization of the works found, it was possible to define 3 categories, which are: 'Teacher Training', 'Theoretical works' and 'Elaboration and analysis of didactic material'. The study made it possible to understand that there are many discussions and publications on the theme addressed, however, the theme is still quite challenging within the school spaces and teacher training. The meeting point between all mapped works permeates the initial and/or continued training of teachers, highlighting the need to think about strategies in this sense.
Keywords: STS; Teaching Chemistry; Science